2021
DOI: 10.35542/osf.io/6zqjr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of COVID on Oral Reading Fluency during the 2020-2021 Academic Year

Abstract: Education has faced unprecedented disruption during the COVID pandemic. Understanding how students have adapted as we have entered a different phase of the pandemic and some communities have returned to more typical schooling will inform a suite of policy interventions and subsequent research. We use data from an oral reading fluency assessment-a rapid assessment taking only a few minutes that measures a fundamental reading skill-to examine COVID’s effects on children’s reading ability during the pandemic. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…In addition, Black, Hispanic/Latino, and American Indian/Alaskan Native students and students in economically disadvantaged schools or neighborhoods experienced the largest declines (Kogan & Lavertu, 2021; Lewis et al., 2021; West & Lake, 2021). Furthermore, students in Grades K-3 were falling behind in the development of essential early reading skills (Domingue et al., 2021; McGinty et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Black, Hispanic/Latino, and American Indian/Alaskan Native students and students in economically disadvantaged schools or neighborhoods experienced the largest declines (Kogan & Lavertu, 2021; Lewis et al., 2021; West & Lake, 2021). Furthermore, students in Grades K-3 were falling behind in the development of essential early reading skills (Domingue et al., 2021; McGinty et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study confirmed these predictions and showed that second and third graders in over 100 United States school districts nationwide fell about 30 percent behind the expected oral reading fluency scores in fall 2020 and that students at lower-achieving schools fell even farther behind ( Domingue et al, 2021 ). A more recent study included data from 5.5 million students in grades 3–8 and measured their reading and math achievements during the 2020–2021 school year ( Lewis et al, 2021 ).…”
Section: Introductionmentioning
confidence: 86%
“…Domingue et al 8 evaluated the impact of COVID-19 on the development of oral reading fluency in students from grades 1 to 3 in more than 100 United States school districts. The survey showed that students in grades 2 and 3 had a shortfall of ∼ 30% compared with a typical year, and it pointed out that students in low-performance districts experienced major shortfalls in learning.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to understand the students' reading development during the period that the schools were closed due to COVID-19 so the teachers can plan strategies for the school year after that. Measuring and monitoring the development of reading fluency are quick and highly predictive strategies for the development of reading and reading-comprehension skills, and are considered by researchers 8 10 strong indicators of proficient reading.…”
Section: Introductionmentioning
confidence: 99%